Mortality and morbidity of major congenital heart disease related to general prenatal screening for malformations. (1st September 2019) - Lytzen, Rebekka; Vejlstrup, Niels; Bjerre, Jesper; Petersen, Olav Bjørn; Leenskjold, Stine; Dodd, James Keith; Jørgensen, Finn Stener; Søndergaard, Lars
Abstract: Background: Major congenital heart diseases (CHD) often demand intervention in the neonatal period. Prenatal diagnosis may improve mortality by eliminating the diagnostic delay; however, there is controversy concerning its true effect. We aimed to evaluate the effect of general prenatal screening on prognosis by comparing a period without general prenatal screening to a period with general prenatal screening. Methods: We conducted a nationwide retrospective study including live born children and terminated fetuses diagnosed with major CHD. Prenatal screening was recommended only in high risk pregnancies between 1996 and 2004, whereas general prenatal screening was recommended between 2005 and 2013. We assessed the influence of general prenatal screening on all-cause mortality, cardiac death, preoperative and postoperative 30-day mortality and complication rate. Results: 1-year mortality decreased over both periods, but the decrease was greater in the screening period (Odds ratio 0.92 (CI 0.83–1.00), p = 0.047). Prenatal detection of major CHD was associated with cardiac death in the period without general screening (Hazard Ratio 2.40 (CI 1.72–3.33), p < 0.001), whereas there was no significant association once general screening was implemented. Similarly, the association between prenatal diagnosis and pre- and postoperative mortality found in the period without general screening was insignificant after the implementation of general screening. Conclusion: Mortality in major CHD decreased throughout the study, especially in the period with general prenatal screening. However, comparing a prenatally diagnosed group with a postnatally diagnosed group is vulnerable to selection bias and proper interpretation is difficult. Highlights: Survival of major congenital heart disease is improving The occurrence of complications is increasing, presumably due to improved survival Prenatal diagnosis of major congenital heart disease is no longer associated with increased cardiac death. Great care must be taken when comparing prenatally diagnosed congenital heart disease with postnatally diagnosed congenital heart disease